Análise das complicações de pacientes idosos no período do pós-operatório até a alta hospitalar - Prince Daiane Felizardo Silva Nascimento (2018)
Introduction: The growth of the demand for health services among the elderly population is directly related to the increase in life expectancy, not only for the Brazilian population, but worldwide. One can highlight the expansion in the number of surgical procedures performed on individuals aged 60 years and the complications expressed by these to an anesthetic surgical intervention. Objective: to Analyze the complications presented by the elderly patients in the postoperative period until hospital discharge. Method: retrospective, longitudinal study, with a quantitative approach. The sample consists of 49 records pertaining to the elderly patients who were accompanied in the Post-Anesthesia Recovery Room in the period from June to September 2013 in a primary study. The data collection of these patients in the period of postoperative - divided into immediate postoperative and late post-operative period until hospital discharge - was performed on medical records from June to August of 2016. The tests Fisher's Exact, Mann-Whitney and McNemar were used for the statistical analysis. Results: Of the 49 records reviewed, more than half (53,1%) were female. The average age was 70 years. 67,3% were submitted to surgery in the region of the abdomen and pelvis. The the highest percentage type of anesthesia was general, with 36,7%. The risk rate was 89,8% of the elderly with ASA II. The complication secretion in the Surgical Wound showed a significant correlation with the type of anesthesia and the duration of anesthesia and surgery. The change of the Heart rate also showed significant correlation with the duration of the surgery. Marginally significant to the complications of hypothermia, pain and intestinal motility dysfunctional demonstrated correlation with the location of the surgery. To compare the complications described in the period of rest in the Post-Anesthesia Recovery Room in from zero to 60 minutes to the Post-operative period until hospital discharge, presented a significant correlation as to the complication of hypertension; hypotension; bradipneia and hypothermia. Conclusion: based on the results exposed, it is permissible to find that the complications present in the elderly in the period of rest in the Post-Anesthetic Recovery Room remain throughout the Postoperative period, especially in the first 48 hours in which the elderly person is in the surgical unit